Beyond Desire? Agency, Choice, and the Predictive Mind. Issue 1 (2nd January 2020) - Clark, Andy
ABSTRACT: 'Predictive Processing' (PP) is an emerging paradigm in cognitive neuroscience that depicts the human mind as an uncertainty management system that constructs probabilistic predictions of sensory signals. Such accounts apply very naturally to perception and have plausible extensions to motor control. But desires and motivations can seem to pose a much greater puzzle, appearing especially resistant to reconstruction by a processing story that appeals to predictions alone. I examine several versions of this worry and show that it is fundamentally misplaced. Desires and motivations are fluently accommodated within the unifying PP schema, where they emerge as webs of prior 'beliefs' that sculpt probabilistic predictions, some of which become positioned (as we shall see) so as to bring about actions. Importantly, a single construct here plays the role of belief and desire. But what results is, perhaps surprisingly, a potentially richer landscape within which to think about agency, control, and choice.